2011
DOI: 10.1073/pnas.1102397108
|View full text |Cite
|
Sign up to set email alerts
|

Mannose receptor polyubiquitination regulates endosomal recruitment of p97 and cytosolic antigen translocation for cross-presentation

Abstract: The molecular mechanisms regulating noncanonical protein transport across cellular membranes are poorly understood. Crosspresentation of exogenous antigens on MHC I molecules by dendritic cells (DCs) generally requires antigen translocation from the endosomal compartment into the cytosol for proteasomal degradation. In this study, we demonstrate that such translocation is controlled by the endocytic receptor and regulated by ubiquitination. Antigens internalized by the mannose receptor (MR), an endocytic recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 38 publications
3
91
0
Order By: Relevance
“…As such, DNGR-1 may be a useful subcellular marker for identifying and characterizing the elusive "cross-presentation compartment" in CD8α + DCs. Of course, our data do not exclude the possibility that DNGR-1 may additionally control the process of cross-presentation, for example, by promoting fusion with the ER-Golgi intermediate compartment (65) or by facilitating translocation of ligand to the cytosol, as recently shown for another myeloid CLR, the mannose receptor (66). Consistent with that notion, the Y7F hemITAM mutant DNGR-1 still localized to the recycling endosomal compartment even though it was impaired in its ability to promote cross-presentation of dead cell-associated antigens (unpublished observation).…”
Section: Discussionmentioning
confidence: 89%
“…As such, DNGR-1 may be a useful subcellular marker for identifying and characterizing the elusive "cross-presentation compartment" in CD8α + DCs. Of course, our data do not exclude the possibility that DNGR-1 may additionally control the process of cross-presentation, for example, by promoting fusion with the ER-Golgi intermediate compartment (65) or by facilitating translocation of ligand to the cytosol, as recently shown for another myeloid CLR, the mannose receptor (66). Consistent with that notion, the Y7F hemITAM mutant DNGR-1 still localized to the recycling endosomal compartment even though it was impaired in its ability to promote cross-presentation of dead cell-associated antigens (unpublished observation).…”
Section: Discussionmentioning
confidence: 89%
“…Low expression levels of CD206 by DC2.4 have also been confirmed by others. 39 Despite the popularity of the DC2.4…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested for mouse DCs that cross presentation of soluble ovalbumin internalized by MR, presumably targeted to early endosomes, is more efficient than cross presentation after fluid phase uptake, which also delivers an unspecified portion of soluble ovalbumin to late endosomes. [16][17][18] Early endosomes also may host the cross presentation of liposome-encapsulated hen egg lysozyme, but in a fashion independent of the proteasomal pathway. 19,20 Experiments where an antigen was coupled to DC-SIGN antibodies also suggested that early endosomal targeting may facilitate cross presentation by human DC-SIGN transgenic mouse DCs.…”
Section: Introductionmentioning
confidence: 99%